Local Government Performance in Federal Nepal: A Systematic Review of Theory, Practice, Challenges, and Future Directions - Adhikari, Shiva Raj; Sharma, Devi Lal; Rodriguez, Joel Mark P.; Paudel, Tek Raj (NPRC Journal of Multidisciplinary Research, 2026)
Background: Nepal's 2015 Constitution established a three-tier federal system, granting significant powers to local governments. However, performance outcomes remain uneven, with limited systematic synthesis of evidence since the federal transition.Objectives: This systematic review synthesizes literature from 2015 to 2026 to evaluate local government performance across service delivery, fiscal management, human resource capacity, accountability, and local economic development; identifies performance determinants; and derives policy implications.Methods: Following PRISMA guidelines, multidisciplinary databases (Web of Science, Scopus, Google Scholar, JSTOR, NepJOL) and grey literature were searched. Thirty-five Nepal-specific empirical studies published since 2015 were selected alongside comparative South Asian and international literature. Qualitative thematic synthesis was employed across five performance dimensions.Findings: Performance is highly imbalanced—urban municipalities show progress in tax collection and digital transparency, while rural governments face staffing shortages, poor financial administration, and elite capture. Human resource shortages constitute the primary cross-cutting challenge, exacerbated by the absence of integrated HR development strategies. Performance struggles stem from cumulative "incremental issues" (procedural delays, jurisdictional ambiguity, coordination gaps) rather than constitutional flaws.Conclusion: Constitutional mandates alone are insufficient. Sustainable local governance requires institutionalizing HR management through formal policies, strengthening intergovernmental coordination, and linking fiscal transfers to performance metrics and citizen feedback.Implication: A formal Local Government Human Resource Development Policy, clarified mandate assignments, and performance-based incentive structures are urgently needed.